Spatial 'Christianisation' in context : strategic intramural building in Rome from the 4th-7th C. AD - Mulryan, Michael, (Archaeopress archaeology., 2014)
This text closely examines the location of the earliest purpose-built Christian buildings inside the city of Rome in their contemporary context. It argues that some of these were deliberately sited by their builders so as to utilise prominent positions within the urban landscape or to pragmatically reuse pre-existing bath facilities for Christian liturgical practice.